Strategic Utilisation of Social Media in Risk Communication - Salim, Faizul Nizam Abu (International Journal of Human and Health Sciences (IJHHS), 2019)
Social media is a communication platform which has witnessed an exponential growth in use and influence in recent years, democratising the communication process especially with the uprising of citizenship journalism and 24-hours journalism. It offers risk/crisis communicators a way of putting into practice those principles which are advocated in good communica t ion practices to be at the core of their risk management and communication practices; at a very low cost, with excellent access to public, great spread and immense speed of spread. Malaysia has an advantage in this area, given that the penetration of social media in the country is 75%, making it 7th overall in the world in January 2018. Approaching this ‘double edge sword’ nature of social media as opportunities rather than challenges, it can be well utilised in risk and crisis communication and help improve emergency preparedness and response, reduce costs of disaster, improve transparency of decisions, and increase the potential of acceptance of outcomes. First and foremost, it is an excellent listening tool to help ‘feel the pulse’ of the public, picking up risk incidents discussed in the social media realm as part of Early Earning Surveillance System (EWARS). It helps to bridge the polarisation and gap between the perception of the public and the perception of the authorities/regulators/experts is a key issue that need to be addressed well in risk communication. Risk and crisis communications are valuable to enhance preparedness and response as they help to raise the level of awareness of citizens and their capacity to take the appropriate measures. With emerging disease, chemica l or radiological threats or even a familiar yearly occurring risk like haze or floods, it is essential to identify effective risk communication strategies for informing both the public and professionals, to promote and achieve appropriate behavioural patterns that mitigate public health risks. The different types of social media and mobile messaging can be complementar y in risk and crisis management. The social networking media can help enhance coordination among volunteers and emergency services. At the same time, content sharing media can assist in conducting situational awareness as many users will share images or videos of how a crisis is evolving in real time. We have seen this umpteenth time, even in Malaysia especially in relation to big incidents that concerns many and evoked emotional response from the public. Examples from some case studies of real incidents will be used to illustrate this; as to share the best practices by the Ministry of Health Malaysia on how social media can be indeed used strategically in risk and crisis communication. International Journal of Human and Health Sciences Supplementary Issue: 2019 Page: 20